Circadian variations influence anxiety-related behaviour, olfaction, and hedonic response in male Sprague–Dawley rats - Weber, Hanna; Statz, Meike; Markert, Franz; Storch, Alexander; Fauser, Mareike (Behavioural brain research, 2024)
Despite the acknowledged impact of circadian rhythms on various aspects of life, behavioural tests with laboratory animals often overlook alignment with their natural activity patterns. This study aims to evaluate the influence of circadian variations on the results, validity, and reliability of different behavioural tests in rats. Three behavioural tests, the Light-Dark Box Test (LDB), assessing anxiety-related behaviour and locomotor activity; the Buried Pellet Test (BPT), revealing olfactory abilities and motivation issues; and the Sucrose Preference Test (SPT), studying the anhedonic response, were employed to encompass multiple daytime-dependent behavioural aspects in male Sprague-Dawley rats. Our findings underscore distinct circadian effects on locomotor activity, exploratory behaviour, olfactory acuity, motivation, and hedonic response. Notably, anxious behaviour remained unaffected by daytime conditions. Furthermore, decreased data variance was found to be correlated with conducting behavioural tests during the subjects’ active phase. This study demonstrates extensive circadian influences on nearly all parameters investigated, coupled with a significant reduction in data variability during the active phase. Emphasising the importance of aligning experimental timing with rats’ natural activity patterns, our results suggest that conducting tests during the active phase of the animals not only refines test sensitivity , reduces stress, and provides more representative data, but also contributes to ethical animal research (3 R) and improves test relevance. This, in turn, enhances the reliability and validity of experimental outcomes in behavioural research and promotes animal welfare. [Display omitted] •Circadian rhythms are often overlooked in behavioural studies on rodents.•Selected behavioural tests (LDB, BPT, SPT) cover diverse behavioural domains.•Significant diurnal influences on locomotion, exploration, olfaction, hedonism.•Enhanced test sensitivity and promoted animal welfare in active period.